AN EXPLORATORY STUDY ON THE EFFECTS OF ERROR MANAGEMENT, INTERNAL AUDİT EFFECTIVENESS AND SELF-EFFICACY ON ERROR HANDLING BEHAVIOR OF ACCOUNTANTS (Third Sector Social Economic Review, 2018)
In this study, it is aimed to evaluate the effects of error management approach, internal audit efficiency and self-efficacy level on the professional error-handling behavior of accountants in an exploratory perspective. It has been determined that resilience and preventive error management approach decreases the probability of making professional errors as a result of evaluating the data compiled by the field survey method with the application of multivariate statistical analysis techniques. However, the error handling behavior is affected by the overall strategy and organizational structure of the business. While the level of self-efficacy changes the effect of the error management on the behavior of accounting errors, it does not significantly affect the effectiveness of the internal audit on professional errors. Evaluations and recommendations were made for the practitioners and researchers in accordance with the determined correlations and findings.
Keywords: Error Management; Internal Auditing; Error Handling; Accounting; Self-Efficacy.